Desconstrução e didática da tradução : a escuta otobiográfica de um ato de tradução - Buosi, Layane Machado (2018)
Understanding the class as a translator act and the teacher as a translation didata, this work poposed to experiment the derridian concept of Translation. To that end, I request to researchers, professors and students of the Federal University of Mato Grosso, Cuiabá campus, that translated the excerpt from a text by Nietzsche. I used the Survey Monkey, an online questionnaire platform, as a tool for this purpose. In a movement of experimentation, from the scripture of these translations, I heard the echoes of my life-experiences, that allowed me to produce another text in co-authorship with these. The listening of the translations was obtained through otobiographic investigation, developed by Monteiro in his doctoral thesis (2004), based on the Nietzschean notion of life-experiences and the concept of otobiographies, proposed by Derrida.